We have two equations x = 3+12y and -2x-y = 3.
In Substitution method, we simplify an expression for one variable and then substitute it into second equation and solve for another variable. Let's solve it below.
x = 3+12y
We can plug it into second equation and solve it for y.
-2(3+12y) -y = 3
-6 -24y -y = 3
-25y = 3 +6
-25y = 9
y = 9 / (-25) = -9/25
Now we can plug it into first equation and solve for x.
x = 3 + 12(-9/25)
x = 3 -108/25
x = (75-108)/25
x = -33/25
Hence, solution to the system of equations is (x,y) = (-9/25 , -33/25).